Manfaat Mentimun (Cucumis Sativus) Perspektif Islam Untuk Kesehatan - Aprilia Dwi Fatimah (Es-Syajar:Journal of Islam, Science and Technology Integration, 2023)
Allah SWT has mentioned in the Qur'an one fruit that is good for the body, namely cucumber Cucumber is a very good fruit and has many benefits, consuming it which contains lots of nutrients and anti-oxidants will be a solution to problems in maintaining a healthy body. There have been many studies on the benefits of cucumber content. The method used in writing this journal is descriptive qualitative and literature review method. The data collection technique used was to collect data from various sources of literature from journals and other literary sources. Allah SWT has mentioned cucumbers in the Al-Qur'an surah AlBaqarah verse 61, besides that it was also narrated by Aisyah R.A, (the wife of Rasulullah SAW) that Rasulullah SAW always ate cucumbers mixed with dates, the benefits according to Aisyah could form a fat body that ideal. Cucumber plants are included in the type of seasonal or short-lived fruit vegetable plants. Cucumber plants grow in vines (creeping) in the form of bushes or shrubs, and the height or length of the plants can reach 2 meters or more. Cucumber is a family of Cucurbitaceae and can be a source of natural antioxidants because it contains vitamin C and flavonoids which can break free radical reactions. Cucumber can be used for treatment, namely to lower blood pressure, cure jaundice, improve urination, maintain bone health, canker sores, anti-cancer, prevent dehydration, hypertension, and destroy kidney stones